International Capital Flows with Limited Commitment and Incomplete Markets - von Hagen, Jürgen (Institutional Knowledge at Singapore Management University, 2011)
Recent literature has proposed two alternative types of financial frictions, i.e., limited commitment and incomplete markets, to explain the patterns of international capital flows between developed and developing countries observed in the past two decades. This paper integrates both types of frictions into a two-country overlapping-generations framework to facilitate a direct comparison of their effects. In our model, limited commitment distorts the investment made by agents with different productivity, which creates a wedge between the interest rates on equity capital vs. credit capital; while incomplete markets distort the investment among projects with different riskiness, which creates a wedge between the risk-free rate and the mean rate of return to risky capital. We show that the two approaches are observationally equivalent with respect to their implications for international capital flows, production efficiency, and aggregate output.